User perception on Smart Card Technology as Service Quality Improvement in Highway Ticketing - Supun, P; Udeshika, R.L (NSBM Green University, 2019)
A smart card is special type of a physical card that has an embedded integrated chip with a high security. Systems that are upgraded with smart cards have been implemented in several key applications, including healthcare, banking, entertainment, and transportation. This study is aimed to find the passenger perception towards “Smart Card” as a service quality enhancement in expressway ticketing and to propose “Smart Cards” for Southern expressway. Primary data gathered using questionnaires by Simple random sampling technique. 300 questionnaires distributed among expressway users and 272 questionnaires received. During data cleaning process only 266 questionnaires retained, where the response rate is 88.6%. Dependent variable of the study is User perception towards smart card technology for toll payments in expressway. After descriptive analysis, hypothesis testing carried out to check the relationship between identified factors and the user perception. Explanatory factor analysis carried out using principle component analysis to identify determinants of user perception. KMO and Bartlett’s test statistics were adequate to perform the factor analysis. 62% of the total variability is explained by the factor model which consists of four factors namely, User benefits of smart cards, efficiency of toll collection process, toll collectors’ behaviour and preference of using smart cards. Regression models being built for each factor to express how demographic factors influenced on each factor. User benefits of smart card experienced is depending on the income level, age and the willing to pay extra service charge. Toll collectors’ behaviour experienced by the users is depending on their age, preferred recharge method and the income level. Efficiency of the toll collecting process experienced by the highway users is depending on the travel purpose and their previous experiences in using Katunayaka expressway. Smart card user preference factor is depending on the age, method of recharging the smart card, frequency of usage of expressway and the previous experiences in using Katunayake express way.
Keywords: Expressway ticketing; Smart Card technology; User perception; Factor Analysis